Methicillin‐resistant Staphylococcus aureus in health‐care workers with cystic fibrosis in Sydney. Issue 9 (29th October 2018) - Song, Yang; Keatley, Lucy Rebecca; Middleton, Peter Gordon
Abstract : Cystic Fibrosis (CF), the most common lethal inherited disorder in Australia, is associated with increased respiratory tract colonization/infection. Given that many adults with CF work as health‐care workers (HCW), which has been associated with an increased risk of methicillin‐resistant Staphylococcus aureus (MRSA) colonization/infection, we examined these risks in 252 adults with CF at our centre between 2001–2015. Demographic and clinical characteristics, including pathogens, were compared for HCW and non‐HCW groups. MRSA colonization/infection was found in 20 subjects, comprising 2/19 HCW, and 18/233 non‐HCW ( p = 0.66). Sixteen of these 20 subjects undertook eradication therapy, with success in 2/2 HCW and 5/14 non‐HCW. This study showed that the rate of MRSA colonization/infection did not differ between adults with CF who work in the health‐care setting versus other areas. This suggests that choosing a health‐care profession does not necessarily result in an increased risk of MRSA colonization/infection for an adult with CF. Abstract : Colonization with MRSA has been noted in a previous study of adults with CF who work in healthcare. Given the increasing number of adults with CF interested in pursuing a health‐care profession, we performed an audit which determined that there was no increased risk of colonization/infection with this organism in our clinic in Sydney.